Organizational Advocacy for Racial Justice - Chad Michael Wertley; Sara J Baker (Journal of Public Interest Communications, 2022)
This study analyzes and classifies the content of organizational advocacy (OA) messages using a thematic content analysis. Data was collected by capturing the Twitter statements made by the top 100 American brands in response to the murder of George Floyd in May 2020. Findings revealed that the statements contained two main themes: framing and acting. Corporations framed their support of racial justice by naming the issue, expressing solidarity, and establishing the shot. Corporations indicated taking specific actions including self-facing (e.g., diversity training), other-facing (e.g., donations), and brand-promoting (e.g., incorporating brand values/slogans/logos). This study adds to OA research as a separate paradigm in public relations (PR) and corporate social responsibility (CSR) and as a framework to evaluate the effectiveness of OA statements.